Contributions of the mammal community, habitat structure, and spatial distance to dung beetle community structure - Bogoni J.A. (2016)
© 2016, Springer Science+Business Media Dordrecht.Dung beetles feed and nest in mammal feces, are influenced by habitat quality and have limited dispersal ability. We hypothesized that dung beetle community structure is affected by mammal composition, habitat structure, and spatial distance, and that these predictors vary among the functional groups in communities. Dung beetles and mammals were sampled using pitfall traps and camera traps, respectively, at 15 Atlantic Forest sites between 2005 and 2013. Habitat structure was described using the point-quadrant method. We utilized descriptive ecological values and used variation partitioning to identify predictors of dung beetle community composition both as a whole, and after organizing the community into functional groups. We recorded 43 dung beetle species and 28 mammal species. Mammal and dung beetle species richness were positively correlated. Mammals and habitat explained the majority of the variation among dung beetle communities, and explanatory values varied substantially when using the functional group approach. Our results indicate that mammals are, indeed, important drivers of dung beetle community structure. Individually, or in combination with habitat structure, mammal composition explained 40 % of the total variation in dung beetle data, i.e., the abundance and species composition of dung beetles and mammals covary. However, herbivorous mammals, medium-sized mammals and omnivorous mammals numerically contributed more than did other groups to the explanation of variation in dung beetle guilds. Habitat structure was an important determinant for dung beetle functional group abundance, and spatial distance influenced covariation between dung beetles and mammals. Thus, the integrity and maintenance of ecological processes in the Atlantic Forest may be dependent on these groups, and further fragmentation, habitat loss and defaunation may increase the sensitivity of this already reduced and threatened biome.